Accurate absolute measurements of the Raman backscattering differential cross-section of water and ice and its dependence on the temperature and excitation wavelength. (June 2017) - Plakhotnik, Taras; Reichardt, Jens
Abstract: Measurements of Raman backscattering spectra between −15 °C and 22 °C in liquid water (including its supercooled state) and in polycrystalline ice (−35 °C to 0 °C) at two excitation wavelengths (407 and 532 nm) are presented. It is found that the spectrum-integrated backscattering cross-section of the 3400 cm −1 band is about 1.2 times larger for ice in comparison to liquid water. The excitation-wavelength dependence of the cross-section in ice is very close to that in water. A discontinuous change of the spectrum is observed upon phase transition at 0 °C. The results are applicable to preliminary calibration of lidar systems designed for water content surveys in the atmosphere. Abstract : Highlights: Absolute Raman backscattering of ice and water accurately measured. Cross-section of water and ice varies similarly when the excitation wavelength changes. Dependence on temperature investigated. Discontinuity upon phase transition.